ANALISIS DAMPAK REMUNERASI DAN LINGKUNGAN KERJA TERHADAP KINERJA DOKTER SPESIALIS DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MEDIASI - Hartati Hartati; Rima Semiarty; Verinita Verinita (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2019)
Performance specialists is something that is very important in order to achieve the objectives Hospital Organization for specialists is the frontline in the service of clients in the hospital so important to know the factors that influence it. The purpose of this study is to describe the impact / influence of the system of remuneration and working environment on the performance and motivation as an intervening or mediating variable in the installation department of obstetrics and child XYZ Hospital Padang. This study uses a quantitative approach to research explanatori. Sampling in the Census, ie as many as 36 people obstetricians and children. Data analysis technique used in this study using the approach Partial Least Square (PLS). The results showed that there was no significant effect between remuneration and the performance of the T statistics amounted to 0.549 (less than 1.96) and the p value 0.002 (greater than 0.05) so the hypothesis is rejected. No significant difference between the work environment and performance statisticsT is smaller than TTable and p value is greater than alpha so the hypothesis is rejected. No significant difference between the motivation to work on performance because the hypothesis is rejected. A significant difference between the remuneration and motivation to work as much as 2.8%. No significant difference between the working environment on work motivation for the hypothesis is rejected. While remuneration on performance mediated by labor motivation does not have a significant effect.